زغبة ؽبقخ اىفدىح ثطشقز لأغش خٍ NiO/FTO اى سَؼشح ثزق خٍْ اىشػ اىن - تواتي حمد, التجاني (university of eloued جامعة الوادي, 2023)
ضط كٔٞ ٛ ًٙ ج ىُ جٌ سْ قٞ ضك ٤ِ ج هُٛحتٙ ج رُ ٤٘س ٝج رُٛ ٣ٍس ٝج ٌُٜ ذٍحت ٤س طُروس NiO/FTO ذط جٍ ٤ً هٓط لِس 0.3M ئ ٠ُ 0.5M ( ، ض ضكٟ ٤ ٛ ًٙ جلأؿ ٤ٗس ج هٍُ ٤وس لأ ٤ًٓى ج ٤ُ٘ NiO ( ػ ٣ٍ ٠ ن ض ٤ٍْد ج كُٔ ِٞ ػ ٠ِ حًٌت ؾَحؾ ٤س طٓ ٤ِس رٓٓواًح ذ FTO ، ٝض صٔ ػ ٤ِٔس ج طُ ٤ٍْد ذح طْهىج ضو ٤٘س ج ج ٤ٔ ٤ٌُ حت ٢ ج كُ جٍ ١ٌ ضكص و ؾٌس ق جٍ زٌ ضر ؾِ 485 و ؾٌس ثٓٞ ٣س، ه حٔ٘ ذك حٓخ ٠حهس ج لُؿٞز ذط ٣ٍوط ٤ ج طُ ٣ٍوس ج ؼُٔطحوز ٝ ج طُ ٣ٍوس ج كُى ٣ػس، ك حٌ صٗ طٗحتؽ ج طُ ٣ٍوط ٤ طٓوح ذٌس ق ٤ع ٣ جلاػط حٔو ػ ٠ِ ج طُ ٣ٍوس ج ؿُى ٣ىز نحٚس ك ٢ ذ ٤ح حٗش ج لُ٘حي ٣س ج طُ ٢ ض طٔح ذو ٤ و ٤ٗح ٝ ػظ ٠ٔ ٝجٞكس، حًٔ أظٜ شٍ طٗحتؽ ضك ٤ِ جلأ ؼٖس ج ٤٘ ٤ُٓ س ظٜٞ ه لأ ٤ًٓى ج ٤ُ٘ ك ٢ ؾ ٤ٔغ ج طُ جٍ ٤ً ج طُٔٓهى سٓ، ٝض ضأ ٤ًى ٛ جً جلأ نلا ج حُٔٗٛىز ذح طْهىج ج ؿُٜٔ جلإ طٌُ ٍٝ ٢ٗ ج حُٔ فْ MEB ٠حهس أٝ ذٌحل ، ض ض ؿٓ ٤ ج هٗلحٜ ك ٢ ه ٤ ج لُ٘حي ٣س ٝج لُحٚ ج طُحه ٢ غٓ ٣َحوز ج طُ ٤ًٍ ،ُ ذ ٤ ح٘ٔ جَوش ه ٤ ٝجلا طٓٛحٚ ٤س. ٝذ ِص ه ٤ سٔ ج لُحٚ ج طُحه ٢ 3.86 eV ػ ى٘ ج طُ ٤ًٍ 0.3M غ ض ح٘هٛص ئ ٠ُ 3.75 eV ػ ى٘ ج طُ ٤ًٍ 0.5M ٤ْ ٌٞ جلأكٟ ك ٢ ج طُطر ٤وحش ج هُٔط لِس ػٓ ج هُلا ٣ح ، ٝ ٤ٗ ٣ ي يُ ئ ٠ُ أ ج طُ ٤ًٍ جلأن ٤ ج ٤ُٗٔٓس ٝؿ ٤ ٍٛح.This study focuses on the analysis of the structural, optical, and electrical properties of NiO/FTO thin films with varying concentrations from 0.3M to 0.5M. The NiO thin films were prepared by depositing the solution onto pre-coated FTO glass substrates using the thermal chemical spray technique at a temperature of 485°C. We calculated the band gap using both conventional and modern methods, and the results from both methods were consistent. The modern method, especially for the transmittance data, proved reliable with clear minimum and maximum values. X-ray analysis confirmed the presence of NiO peaks in all used concentrations, which was also observed through scanning electron microscopy (SEM). The transmittance and band gap values decreased with increasing concentration, while the Orbach energy and absorbance values increased. The band gap value was 3.86 eV at a concentration of 0.3M, and it decreased to 3.75 eV at a concentration of 0.5M. This indicates that the higher concentration is more suitable for various applications such as solar cells and others.
مذكرة ماستر فيزياء
Keywords: جلأؿ ٤ٗس ج هٍُ ٤وس، ج ج ٤ٔ ٤ٌُ حت ٢ ج كُ جٍ ١ٌ، ج لُحٚ ج طُحه ٢; Thin films, thermal chemical spray, band gap, NiO FTO.